1978
DOI: 10.1002/jpln.19781410104
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptionsisothermen als Regelgrößen beim Transport von Schwermetallen in Böden

Abstract: Adsorption isotherms as regulators controlling heavy metal transport in soils The adsorption and desorption of Pb2+ and Cd2+ from equilibrium solutions with heavy metal contents up to 5000 μg/1 were determined in bulk experiments for soil samples from an acid Braunerde developed in loess loam, taken from the humic surface layer of the mineral soil (0–10 cm) and from the subsoil fairly free from organic matter (30–40 cm). Pb and Cd in solutions were determined by flameless atomic absorption spectroscopy. Pb was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Long-term exposure for more than a year did not significantly change this desorption pattern. Mayer (1978) found no irreversibility for two acid German soils. Figure 4.11 shows desorption data for the same soils, but here the desorption takes place at different conditions with respect to pH and Ca concentration compared with the adsorption.…”
Section: Reversibilitymentioning
confidence: 93%
“…Long-term exposure for more than a year did not significantly change this desorption pattern. Mayer (1978) found no irreversibility for two acid German soils. Figure 4.11 shows desorption data for the same soils, but here the desorption takes place at different conditions with respect to pH and Ca concentration compared with the adsorption.…”
Section: Reversibilitymentioning
confidence: 93%
“…Several authors have suggested methods for the fractionation of heavy metals in solid phases (Elsokkary and Lag, 1978;Fischer and Fechter, 1982;Kuo et aI., 1983;Shuman, 1982Shuman, , 1983Sposito et aI., 1982;see also Forstner, this volume). Also, successful computer programs have been developed for modeling the distribution of metal species in soil solutions (Jenne 1979;Sposito, 1981;Sposito and Bingham, 1981) and metal transport through the soil profile (Mayer, 1978;Poelstra et aI., 1979). Also, successful computer programs have been developed for modeling the distribution of metal species in soil solutions (Jenne 1979;Sposito, 1981;Sposito and Bingham, 1981) and metal transport through the soil profile (Mayer, 1978;Poelstra et aI., 1979).…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of metal species in soil solutions methods are used which are based on more profound analytical background ( Gregson and Alloway, 1984;Jeffery and Uren, 1983;McBride and Bouldin, 1984;Tills and Allowuy, 1983). Also successful computer programs are developed for modelling metal speciation in soil solutions (Jenne, 1979;Sposifo and Bingham, 1981) and metal transport through the soil profile (Mayer, 1978;Poelstra et al, 1979).…”
Section: Introductionmentioning
confidence: 99%